Manure helps feed the world: Integrated Manure Management demonstrates manure is a valuable resource - Teenstra, E.; Andeweg, K.; Vellinga, Theun V. (2016)
Overview of Integrated Manure Management Integrated Manure Management is the optimal handling of livestock manure from collection, through storage and treatment up to application (crops and aquaculture). Through this process it is possible to prevent nutrient losses to a large extent under the site-specific circumstances.